Realizations of affine Lie algebras - Futorny, V. (Algebra and Discrete Mathematics, 2005)
This is an expository paper on some realizations of affine Lie algebras and their representations in terms of differential operators. In particular we recall the classical construction of Wakimoto modules and its recent generalization - Intermediate Wakimoto modules [CF].